Cutis marmorata telangiectatica congenita unresponsive to propranolol. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2013)
A little girl aged 3 months was first observed due to an angioma of the face. Her mother reported that at birth there was a visible pink patch about 1.5 cm in diameter on the face and a bluish spot on the back. The patch of the face quickly became raised and redder, while that of the back remained flat and virtually unchanged. The dermatological examination (Fig. 1 ) showed in the left mandibular region a 3 cm in diameter nodule, raised for 1 cm, red in the center to about 2 cm in diameter and bluish in the periphery; the nodule was warm and could be depressed. In the right paravertebral and costal region there were two areas of bluish and cross-linked skin. We diagnosed hemagioma associated with cutis marmorata telangiectatica congenita (CMTC ) and started treatment with propranolol 2mg/kg per day in two divided doses. At the age of 1 year after 9 months of treatment hemangioma was reduced by 80% both in its deep raised and superficial red component (Fig. 2), while the CMTC was unchanged (Fig. 3).